The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/ases.13136
|View full text |Cite
|
Sign up to set email alerts
|

3D printed kidney model could be an important educational tool for residents

Abstract: Introduction This study aimed to evaluate whether it is useful for junior physicians to use a three‐dimensional (3D) kidney model when evaluating the R.E.N.A.L. nephrometry score. Materials and Methods An expert and four urology residents retrospectively evaluated the R.E.N.A.L. nephrometry scores of 64 renal tumors (62 patients) that underwent robot‐assisted partial nephrectomy at our hospital. The expert evaluated 64 R.E.N.A.L. nephrometry scores with computed tomography (CT), whereas four residents evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In navigation for PN, these models have been used for preoperative training and surgical simulations, with reports indicating significantly less blood loss compared to when navigation was not performed [17] . There have also been reports of a significant decrease in warm ischemia time when 3D printed models were employed for preoperative planning and intraoperative navigation [18] . In addition, it has been reported that they are not only useful for patient education but also for resident education, and they are beneficial in achieving the trifecta during the initial implementation of RAPN [19,20] .…”
Section: D Printed Modelmentioning
confidence: 99%
“…In navigation for PN, these models have been used for preoperative training and surgical simulations, with reports indicating significantly less blood loss compared to when navigation was not performed [17] . There have also been reports of a significant decrease in warm ischemia time when 3D printed models were employed for preoperative planning and intraoperative navigation [18] . In addition, it has been reported that they are not only useful for patient education but also for resident education, and they are beneficial in achieving the trifecta during the initial implementation of RAPN [19,20] .…”
Section: D Printed Modelmentioning
confidence: 99%
“…However, the use of 3D printing models provides a noninvasive environment for residents to gain valuable training and accumulate experience. Yamazaki et al 109 had four residents retrospectively assess R.E.N.A.L scores in 64 patients with renal tumors who underwent robot-assisted partial nephrectomy. Thirty-two patients were evaluated using CT alone, and the rest were evaluated using CT and 3D renal models, suggesting that the accuracy of R.E.N.A.L renal measurement scores of 3D models and CT was significantly higher than that of CT alone.…”
Section: ■ Educationmentioning
confidence: 99%
“…The application of 3DP models bridges the gap between two-dimensional (2D) imaging and realistic anatomy, as it accurately reproduces anatomical structures and pathologies, thereby providing more tangible information than conventional imaging data [ 19 ]. 3DP models also appear to be a significantly more useful and cost-effective technique than traditional cadaveric models in medical education [ 20 ], such as those used in undergraduate dentistry training [ 4 ], urology residents [ 21 ], first-year medical students [ 22 ], craniofacial traumas [ 23 ], oral and cranio-maxillofacial surgery [ 24 ]. However, recent SBME changes regarding 3DP models have focused only on undergraduate medical education [ 25 ].…”
Section: Introductionmentioning
confidence: 99%